ASSESSMENT OF IMMUNOLOGICAL TEST RESULTS IN DIAGNOSING PATIENTS WITH ALLERGIC RHINOSINUSITIS - Akhmedova Ziyodakhon Anvar qizi (American Journals Publishing, 2025)
Allergic rhinosinusitis is an inflammatory condition of the nasal mucosa triggered by exposure to allergens, mediated primarily by immunoglobulin E (IgE). Understanding the underlying pathogenic mechanisms is essential for prescribing effective and targeted therapy [18]. The pathogenesis of allergic rhinosinusitis is based on the development of an IgE-mediated hypersensitivity immune response initiated by allergens penetrating the nasal mucosa. This process occurs in two phases: early and late, which define the nature and progression of clinical symptoms. Both phases involve the activation of mast cells, eosinophils, lymphocytes, and basophils. The initial phase of allergic hyperreactivity is characterized by plasma exudation containing high levels of biologically active substances such as histamine, kinins, and immunoglobulins. Consequently, nasal congestion and rhinorrhea are prominent symptoms in the early phase. During the exudation process, histamine released onto the nasal mucosa irritates nerve endings through interepithelial junctions, causing itching and sneezing in the nose [12,17].